"Just sit and eat." Adult and Child Mealtime Responsibilities in Early Care and Education Centers During COVID-19 in Florida. Issue 5 (3rd September 2022) - Farrer Mackie, Joanna; Marshall, Jennifer; Gray, Heewon L.; Himmelgreen, David; Alkon, Abbey; Kirby, Russell S.
ABSTRACT: Most young children in the United States attend early care and education (ECE) programs, in which they eat 3–4 times daily. 'Division of responsibility' between adult and child means the adults are responsible for what, when and where, and the child is responsible for whether, what and how much to eat. A balanced division of responsibility can support children's development of healthy eating competency. This paper aims to describe division of responsibility during mealtimes during COVID-19 in Florida using a cross-sectional, mixed methods design. Questions were developed based on Trust Model and Social Cognitive Theory. A survey was completed by 759 ECE directors and 431 teachers, and 29 teachers completed in-depth interviews. COVID-19 increased teacher mealtime responsibilities. Most (95%+) ECE teachers provided meals at the same time and place daily (when and where) . Children determined what and how much they ate, but did not serve or handle food. Implications include modifying mealtime routines to minimize the risk of COVID-19 and support healthy eating with a balanced division of responsibility.